Categorization of Cytochrome P4502D6 Activity Score by Urinary Amphetamine/Methamphetamine Ratios - Jatuporn Chaichana; Manee Khamenkhetkarn; Thanapat Sastraruji; Tawachai Monum; Timothy E. O’Brien; Yutti Amornlertwatana; Churdsak Jaikang (Metabolites, 2022)
Methamphetamine (MA) level in urine has been used for judgment in MA consumption. Metabolism and intoxication of MA are correlated with the activity of cytochrome P450 2D6 (CYP2D6). The activity score (AS) is a potential tool for predicting exposure and personalized dose of drugs metabolized by CYP2D6. Prediction of the CYP2D6 activity score might be described as MA intoxication. The objective of this study was to categorize the CYP2D6 activity score using the urinary amphetamine (AM)/MA ratio. Urine samples (n = 23,258) were collected. The levels of MA and AM were determined by a gas chromatography–nitrogen–phosphorus detector. The log AS was calculated by an AM/MA ratio and classified into four groups following the percentile position: lower than the 2.5th, the 2.5th–the 50th, the 50th–97.5th, and greater than the 97.5th percentile, respectively. The AS value for males presented was less than 0.024, 0.024–0.141, 0.141–0.836, and greater than 0.836. Meanwhile, the AS values were revealed to be lower than 0.023, 0.023–0.148, 0.148–0.850, and higher than 0.850 for females. The AS value of CYP2D6 can be applied to describe the toxicity of MA in forensic crime scenes and relapse behavior.